Horizontal transmission of foot‐and‐mouth disease virus O/JPN/2010 among different animal species by direct contact - Fukai, Katsuhiko; Nishi, Tatsuya; Morioka, Kazuki; Yamada, Manabu; Yoshida, Kazuo; Yamakawa, Makoto (Transboundary and Emerging Diseases, 2020)
Foot‐and‐mouth disease (FMD) is highly contagious and easily transmitted among species of cloven‐hoofed animals. To investigate the transmission of FMD virus (FMDV) among different animal species, experimental infections using the O/JPN/2010 strain were performed in cows, goats and pigs. One cow or two goats/pigs were housed with a different species of inoculated animals, and clinical observations, virus shedding and antibody responses were analysed daily. Whilst all cows and goats were infected horizontally by contact with inoculated pigs, transmission from cows to goats/pigs and from goats to cows/pigs was not observed in all in‐contact animals. In particular, no pigs were infected horizontally by contact with inoculated goats. Comparison with our previous study on experimental infections among animals of the same species indicates that horizontal transmission occurred more easily between animals of the same species than between those of the different species. These findings will be useful for establishing and performing species‐specific countermeasures in farms and regions where multiple species of animals coexist in potential future outbreaks.